2015
DOI: 10.1002/jmri.25041
|View full text |Cite
|
Sign up to set email alerts
|

T2* mapping at 3.0T MRI for differentiation of papillary thyroid carcinoma from benign thyroid nodules

Abstract: T2* mapping can potentially provide quantitative information to separate PTC from benign thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
(45 reference statements)
0
22
0
Order By: Relevance
“…One previous study showed that only 26/40 patients had images that could be interpreted because of distortion [ 8 ]. Another study showed that patient motion was the major factor of exclusion due to breathing, swallowing, and coughing [ 2 ]. In addition, the b value is a critical factor affecting image quality and ADC values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous study showed that only 26/40 patients had images that could be interpreted because of distortion [ 8 ]. Another study showed that patient motion was the major factor of exclusion due to breathing, swallowing, and coughing [ 2 ]. In addition, the b value is a critical factor affecting image quality and ADC values.…”
Section: Discussionmentioning
confidence: 99%
“…About, 19–67% of the healthy, asymptomatic individuals are diagnosed with nodules of the thyroid [ 1 ]. Malignant thyroid nodules account for 5–15% of all thyroid nodules [ 2 , 3 ]. With the rapid economic development of China, healthcare access and screening are improving in China and the detection and prevalence of thyroid nodules is reaching epidemics proportions, from 8% in 2002 to 25% in 2013 [ 4 ], as has been observed in developed countries [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…T 1 and T 2 relaxation time constants have been shown to correlate to fibrosis, cartilage integrity, and tumor response either de novo or following administration of intravenous contrast . T 2 * relaxation is a susceptibility‐dependent extension of T 2 relaxation that can be used in the detection of brain microbleeds, tumors, and iron deposition . Since T 1 , T 2 , and T 2 * are all affected by changes in tissue structure or composition, a multi‐parametric approach to relaxation time constant mapping could provide more robust detection of tissue changes.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid MRI is a noninvasive examination technique without the risk of radiation and contrast medium injection ( 4 , 5 ). In recent years, thyroid MRI has been increasingly used in the diagnosis of thyroid diseases ( 4 , 5 , 6 , 7 , 8 , 9 ). For example, diffusion-weighted MRI was well applied in identifying autoimmune thyroid disease and malignant thyroid nodules ( 4 , 5 , 6 , 7 , 8 , 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MRI has been increasingly used for identifying thyroid diseases ( 4 , 5 , 6 , 7 , 8 , 9 ). Longitudinal relaxation time mapping (T1-mapping) measured by MRI is a new technique for assessing fibrosis of some organs, such as the heart and liver ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%